Проблема знания в философии Абая - Феталиева, Н.Ю. (Изд-во КарГУ, 2010)
Мақалада қазақ ойшыл Абай Құнанбаевтың дүниетанымдағы бір мəселе — білім мəселесі талқыланады. Ойшыл дəстүрлі білімді (нақлия) жəне философиялық білімді (ғақлия) бөлсе, адамзат өркениетіне соңғысы пайда əкеледі. Абай Құнанбаев білімге жету жолын көрсетіп, толық адам туралы ілімді құрастырады. The problem of philosophical news of Kazakh thinker Abay Konunbayew is analyzed in this article. It is the problem of knowledge in his philosophy. The thinker distinguishes traditional (it is a sum of knowledge) and philosophical knowledge (it is a wisdom), because it is able to give benefit to the humanity. Abay shows the ways of the achievement knowledge and elaborates the doctrine about perfect person.
Keywords: великий казахский мыслитель; учение; категория; человек; духовные потребности; бытие; смысл жизни; казахская философия; эпистемология; невежество; любовь; бог